Optical nanomanipulation - Andrews, David L., 1952-; Bradshaw, David S. (IOP (Series). Release 22., 2022)
The extended and updated second edition of this book expands its broad survey of the wide-ranging field of optical nanomanipulation. It aims to establish and differentiate the physical principles of this phenomenon, while providing a snapshot portrait of many of the most prominent and up-to-date applications.